From family farming to micro-enterprises of monoculture. Socio-territorial restructuring in the northern highlands of Ecuador. - Lechon Sanchez, Luis Wilson (2019)
In the rural communities of the Parish of González Suárez and Ayora of the Province of Imbabura and Pichincha, respectively, a large number of employees who managed to accumulate capital have decided to become micro-entrepreneurs of strawberry monocultures. This change in the use of the land has caused a socio-territorial restructuring provoking in the communities; environmental, sociocultural and economic impacts, thus generating a set of tensions on the vision of the land, territory and natural resources. This has opened reflections on productivity and profit, on the practice of community values ??and the sense of peasant family agriculture for indigenous communities. And, considering that the monoculture has irreversible effects on the land, they put into the debate the urgent need to incorporate in the agenda of the organizations and the indigenous movement the demand for the construction of sustainable rural territories, together with the State and the authorities local.